Frequency drift rates of powerful decameter Type III bursts - Boiko, A.I.; Mel'nik, V.N.; Konovalenko, A.A.; Rucker, H.O.; Abranin, E.P.; Dorovskyy, V.V.; Lecacheux, A. (Advances in Astronomy and Space Physics, 2011)
We report on the observations of powerful (fluxes are larger than 10⁻¹⁹ W m⁻² Hz⁻¹) solar Type III bursts at frequencies 10 − 30 MHz. Recordings of 163 bursts, observed in July 2002 and of 231 bursts observed in August 2002 are investigated. The main properties of these Type III bursts (frequency drift rate, duration, flux, frequency bandwidth) are analyzed. In present report we pay more attention to consideration of frequency drift rate. A great difference between the observed and the well-known empirical frequency dependencies of Type III bursts drift rate is determined. A linear approximation for the drift rate versus frequency is found. It indicates, that solar corona above active regions has exponential density distribution. We consider that drift rate value depends on the position of an active region on the solar disc.